You just don't listen a parent's guide to improving communication with young people - Hayman, Suzie (Vermilion, 1998)
The author examines parental concerns and expectations and analyses how parents and children communicate during the teenage years. She attempts to identify the real concerns behind the heated words that are spoken at this sensitive time, with a view to building bridges between the generations.